2016
DOI: 10.4049/jimmunol.1601083
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Death Ligand 1 Plays a Neuroprotective Role in Experimental Autoimmune Neuritis by Controlling Peripheral Nervous System Inflammation of Rats

Abstract: Programmed death 1 (PD-1; CD279), a member of the CD28 family, is an inhibitory receptor on T cells and is responsible for T cell dysfunction in infectious diseases and cancers. The ligand for PD-1, programmed death ligand 1 (PD-L1; also known as B7-H1, CD274), is a member of the B7 family. The engagement of PD-1 with programmed death ligand can downregulate autoreactive T cells that participate in multiple autoimmune diseases. Experimental autoimmune neuritis (EAN) is an animal model of Guillain-Barré syndrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 46 publications
2
26
0
Order By: Relevance
“…It has been reported that in patients with breast cancer and CRC, Tregs co‐express high levels of PD‐1 and CTLA‐4 within the TME to create an immune‐subversive environment for the survival of tumor cells . PD‐L1 can alter T‐cell differentiation pathway by reducing CD4 + IFNγ + Th1 and CD4 + IL17 + Th17 and increasing Treg activation probably by inhibiting the PI3K/AKT/mTOR signaling pathway . Additionally, it has been reported that upregulation of PD‐L1 in tumor cells and FOXP3 in intratumoral Tregs synergistically upregulates their expression in the TME of patients with breast cancer, which favors tumor immune evasion …”
Section: Programmed Cell Death‐1 (Pd‐1) and Its Ligand‐1 (Pd‐l1)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that in patients with breast cancer and CRC, Tregs co‐express high levels of PD‐1 and CTLA‐4 within the TME to create an immune‐subversive environment for the survival of tumor cells . PD‐L1 can alter T‐cell differentiation pathway by reducing CD4 + IFNγ + Th1 and CD4 + IL17 + Th17 and increasing Treg activation probably by inhibiting the PI3K/AKT/mTOR signaling pathway . Additionally, it has been reported that upregulation of PD‐L1 in tumor cells and FOXP3 in intratumoral Tregs synergistically upregulates their expression in the TME of patients with breast cancer, which favors tumor immune evasion …”
Section: Programmed Cell Death‐1 (Pd‐1) and Its Ligand‐1 (Pd‐l1)mentioning
confidence: 99%
“…17,50 PD-L1 can alter T-cell differentiation pathway by reducing CD4 + IFNc + Th1 and CD4 + IL17 + Th17 and increasing Treg activation probably by inhibiting the PI3K/AKT/ mTOR signaling pathway. 78 Additionally, it has been reported that upregulation of PD-L1 in tumor cells and FOXP3 in intratumoral Tregs synergistically upregulates their expression in the TME of patients with breast cancer, which favors tumor immune evasion. 79 EFFECT OF ANTI-PD-1 AND ANTI-PD-L1 ANTIBODIES ON TREGS PD-1/PD-L1 axis supports tumor immune evasion in many cancers, and blockade of this interaction using monoclonal antibodies against PD-1 or PD-L1 can lead to restoration of effector T-cell functions.…”
Section: Ctla-4: the First Clinically Validated Immune Checkpoint Molmentioning
confidence: 99%
“…In addition, our team and others reported that the engagement of PD-L1 with its receptor on T cells led to the development of functional Treg cells and the downregulation of T-cell responses. 29,30 PD-L1 administration significantly alleviated symptoms and suppressed disease progression in murine models of autoimmune disorders and graft-versus-host disease by promoting the development of Treg cells and inhibiting the differentiation of Th17 cells. [13][14][15]30,31 Consistent with those reports, we showed that the underlying mechanism for improving the aftermath of ICH involves a change in the balance of Treg/Th17 cells.…”
Section: Discussionmentioning
confidence: 98%
“…The supernatants were harvested for assay. Cytokines in supernatants, including IL-1b, IL-6, IL-10, IL-12, TNF-a, and TGF-b, were analyzed by using a multi-analyte ELISArray kit (Qiagen) according to the instructions of manufacturer as previously described (38).…”
Section: Cytokine Assaymentioning
confidence: 99%